Dr. William Davis in Account with George Booth, Deceased (1819)
A list of charges and accounts between George Booth, father of James Curtis Booth (1810-1888), and William Morris Davis (1815-1891), a member of the United States House of Representatives.
Keywords: Booth, James Curtis, 1810-1888; Davis, William Morris, 1850-1934; Booth, George; Accounting